Economic distress and farmer suicides in India: an econometric investigation - Hebous, Sarah; Klonner, Stefan (Discussion paper series, 2014)
This paper empirically analyzes sources of extreme economic distress in rural India. We use district-level data on farmers' suicides in two major states during the years 1998 to 2004 to estimate the effects of transitory economic shocks and structural change in agriculture on the incidence of suicides in farm households. To elicit the causal effect of transitory economic shocks on suicides, we use rainfall conditions as an instrumental variable. For the state of Karnataka, where rainfall and poverty were especially variable around the turn of the millennium, we find that transitory spikes in poverty caused by a lack of rainfall increase suicides among male and decrease suicides among female members of farm households. According to our point estimates, a poverty increase of one percent increases male suicide mortality by 0.57 and decreases female suicide mortality by 1.05 percent. Given that suicides among male farmers are four times as frequent as among females on average, the combined causal effect of a poverty shock on suicides in farm households is positive. We also find that a shift from subsistence crops to cash crops, especially cotton, is associated with a decrease in male suicides.